The factors influencing drug abuse problems amongst youths: a case study at Pengasih Rehabilitation Center, Bukit Tunku, Kuala Lumpur / Mohd Hafizi Hashim and Siti Hajar Abd Majid - Hashim, Mohd Hafizi; Abd Majid, Siti Hajar (Faculty of Administrative Science and Policy Studies, 2013)
This study focus on identifying the factors that contributes to the drug abuse problems amongst youth. There are four factors that have been identified and examined by the researchers which are relieve stress, peer pressure, family problems and curiosity of youth. This research is carried out to identify the relationship between the factors and drug abuse problems. This study was carried out at PENGASIH Rehabilitation Center Malaysia, Bukit Tunku, Kuala Lumpur. The sample size of this research is 38 respondents which are selected by the researchers by using the stratified sampling from the population of 60 residents of that rehabilitation center. The respondents are selected from two groups of residents at PENGASIH which are pre-treatment group and post-treatment group. In this research, descriptive statistics has been used to describe the gathered data and inferential statistics also was employed in order to determine the relationship between the dependent variable and independent variables. The findings show that there are significant positive relationship between the dependent variable and those independent variables. It means that the factors of relieve stress, peer pressure, family problems and curiosity of youth give significant impacts towards the problems of drug abuse amongst youth especially in PENGASIH Rehabilitation Center Malaysia, Bukit Tunku, Kuala Lumpur.